A Diagnostic Method for a Multi-Connected PEM-type Electrolysis System by Current Sweeping - Jiachen GE; Shinji FUJITA; Akira GUNJI; Motoyuki HIROOKA; Masatoshi SUGIMASA; Hiromu KAKUYA (Electrochemistry)
Water electrolysis is a power-to-gas technology that can be used to decrease the effect of global warming. To reduce its overall cost, we have designed a water electrolysis system containing serially connected water electrolyzers that reduce the site area and increase energy efficiency. One of the issues remaining to be solved is to develop a method that can diagnose the degradation state of the water electrolyzer during operation without significantly changing the current supply. In this study, a diagnostic method, named the sweep method, was developed. A typical procedure of this method is described as follows. A linear sweeping current is applied to the multi-connected water electrolysis system. Then, swept current and response voltage measurements are collected and subjected to linear and nonlinear regression based on an equivalent circuit, -R0-(R1, C1)-, to obtain its circuit parameters. The electrical resistance R0 is elected as the evaluation criteria of the degradation, and the diagnostic results of sweep method are found to be close to those of an impedance analysis. As the method can be conducted without a significant current change, we believe that it can be applied to a large-scale water electrolysis system.